Oral cavity lesions: A study of 21 cases - Pudasaini, S; Baral, R (Journal of Pathology of Nepal, 2011)
Background: Development of lesions in the oral cavity is strongly linked with smoking and alcohol consumption. Non neoplastic lesions are mainly inflammatory conditions. It has been seen that the benign lesions are more common than malignant. Materials and methods: This was a retrospective study carried out in the Department of Histopathology of Helping Hands Community Hospital during a period of one and a half years from January 2009 to June 2010. The study included 21 cases of oral cavity lesions. Results: The most common site was lip with 9 cases (42.8%) followed by buccal cavity with 5 cases (23.8%). Out of the 21 cases of oral cavity lesions, 20 cases (95.2%) were benign and 1 case (4.8%) was malignant. The malignant lesion was a case of squamous cell carcinoma of soft palate. Conclusion: Any oral cavity lesion should have a tissue diagnosis for rational management of the case and to avoid mutilating surgery. Keywords: Oral cavity; Fibroma; Mucocele DOI: 10.3126/jpn.v1i1.4452 Journal of Pathology of Nepal (2011) Vol.1, 49-51